Mapping the link between socio-economic factors, autistic traits and mental health across different settings - Del Bianco, Teresa; Lockwood Estrin, Georgia; Tillmann, Julian; Oakley, Bethany F; Crawley, Daisy; San José Cáceres, Antonia; Hayward, Hannah; Potter, Mandy; Mackay, Wendy; Smit, Petrusa; du Plessis, Carlie; Brink, Lucy; et al. (Autism, 2023)
Autistic individuals experience higher rates of externalising and internalising symptoms that may vary with environmental factors. However, there is limited research on variation across settings that may highlight common factors with globally generalisable effects. Data were taken from two cohorts: a multinational European sample (n = 764; 453 autistic; 311 non-autistic; 6-30 years), and a South African sample (n = 100 non-autistic; 3-11 years). An exploratory factor analysis aggregated clinical (Verbal Comprehension and Perceptual Index), adaptive traits (Vineland Adaptive Behaviour Scale) and socio-economic variables (parental employment and education, home and family characteristics) in each cohort separately. With regression, we investigated the effect of these factors and autistic traits on internalising and externalising scores (measured with the Strengths and Difficulties Questionnaire). Cohorts showed similar four-factor structures (Person Characteristics, Family System, Parental and Material Resources). The ‘Family System’ factor captured family size and maternal factors and was associated with lower internalising and externalising symptoms in both cohorts. In the European cohort, high autistic traits reduced this effect; the opposite was found in the South Africa cohort. Our exploratory findings from two separate analyses represent consistent evidence that Family System is associated with internalising and externalising symptoms, with a context-specific impact in persons with high autism traits. - Lay Abstract - Autistic individuals are more likely than non-autistic individuals to experience a mental health condition in their lifetime, and this includes externalising and internalising symptoms. We know very little about how different environments and family conditions impact these symptoms for autistic individuals. Improving our understanding of these relationships is important so that we can identify individuals who may be in greater need of support. In this article, we seek to improve our understanding of how environmental and family conditions impact externalising and internalising symptoms in autistic and non-autistic people. To do this, we conducted analyses with two cohorts in very different settings - in Europe and South Africa - to ensure our findings are globally representative. We used advanced statistical methods to establish environmental and family conditions that were similar to each other, and which could be combined into specific ‘factors’. We found that four similar ‘factors’ could be identified in the two cohorts. These were distinguished by personal characteristics and environmental conditions of individuals, and were named Person Characteristics, Family System, Parental and Material Resources. Interestingly, just ‘Family System’ was associated with internalising and externalising symptoms, and this was the same in both cohorts. We also found that having high traits of autism impacted this relationship between Family System and mental health conditions with opposite directions in the two settings. These results show that characteristics in the Family System are associated with internalising and externalising symptoms, and autistic persons are particularly impacted, reinforcing the notion that family stressors are important to consider when implementing policy and practice related to improving the mental health of autistic people.
EU-AIMS LEAP Team: Jessica Faulkner, Sarah Baumeister [und 14 weitere]
Erstveröffentlichung: 12. Oktober 2023
Gesehen am 05.03.2024